A method to synchronize signals from multiple patient monitoring devices through a single input channel for inclusion in list‐mode acquisitions. Issue 12 (15th November 2013) - O'Connor, J. Michael; Pretorius, P. Hendrik; Johnson, Karen; King, Michael A.
Abstract : Purpose: : This technical note documents a method that the authors developed for combining a signal to synchronize a patient‐monitoring device with a second physiological signal for inclusion into list‐mode acquisition. Our specific application requires synchronizing an external patient motion‐tracking system with a medical imaging system by multiplexing the tracking input with the ECG input. The authors believe that their methodology can be adapted for use in a variety of medical imaging modalities including single photon emission computed tomography (SPECT) and positron emission tomography (PET). Methods: : The authors insert a unique pulse sequence into a single physiological input channel. This sequence is then recorded in the list‐mode acquisition along with the R‐wave pulse used for ECG gating. The specific form of our pulse sequence allows for recognition of the time point being synchronized even when portions of the pulse sequence are lost due to collisions with R‐wave pulses. This was achieved by altering our software used in binning the list‐mode data to recognize even a portion of our pulse sequence. Limitations on heart rates at which our pulse sequence could be reliably detected were investigated by simulating the mixing of the two signals as a function of heart rate and time point during the cardiac cycle at which our pulse sequence is mixed with the cardiac signal. Results: : The authors have successfully achieved accurate temporal synchronization of our motion‐tracking system with acquisition of SPECT projections used in 17 recent clinical research cases. In our simulation analysis the authors determined that synchronization to enable compensation for body and respiratory motion could be achieved for heart rates up to 125 beats‐per‐minute (bpm). Conclusions: : Synchronization of list‐mode acquisition with external patient monitoring devices such as those employed in motion‐tracking can reliably be achieved using a simple method that can be implemented using minimal external hardware and software modification through a single input channel, while still recording cardiac gating signals.